2021
DOI: 10.3389/fbioe.2021.646690
|View full text |Cite
|
Sign up to set email alerts
|

Bovine-Derived Xenografts Immobilized With Cryopreserved Stem Cells From Human Adipose and Dental Pulp Tissues Promote Bone Regeneration: A Radiographic and Histological Study

Abstract: Adipose tissue-derived stem cells (ADSCs) and dental pulp stem cells (DPSCs) have become promising sources for bone tissue engineering. Our study aimed at evaluating bone regeneration potential of cryopreserved ADSCs and DPSCs combined with bovine-derived xenografts with 10% porcine collagen. In vitro studies revealed that although DPSCs had higher proliferative abilities, ADSCs exhibited greater mineral depositions and higher osteogenic-related gene expression, indicating better osteogenic differentiation pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…In the micro-CT analysis, black-and-white tomogram images can be converted into equal density pseudocolour images and the boundary between bone/residual graft can be calibrated. For example, Zhu et al [ 65 ] defined tissues with CT values between 700 and 2000 Hounsfield unit (Hu) as the new bone. Tissues with CT values more than 2000 Hu were defined as the residual graft/scaffold after calibration.…”
Section: Resultsmentioning
confidence: 99%
“…In the micro-CT analysis, black-and-white tomogram images can be converted into equal density pseudocolour images and the boundary between bone/residual graft can be calibrated. For example, Zhu et al [ 65 ] defined tissues with CT values between 700 and 2000 Hounsfield unit (Hu) as the new bone. Tissues with CT values more than 2000 Hu were defined as the residual graft/scaffold after calibration.…”
Section: Resultsmentioning
confidence: 99%
“…Zhu Y et al, compared ADSCs and DPSCs for bone regeneration using bovine-derived xenografts with 10% porcine collagen as a scaffold. The study found that although DPSCs had higher proliferative abilities, ADSCs exhibited greater mineral depositions and higher osteogenic-related gene expression, indicating a better osteogenic differentiation potential of ADSCs [ 201 ]. After applying cryopreserved ADSCs and DPSCs in a critical-size calvarial defect model, both cryopreserved mesenchymal stem cells significantly improved the bone volume density and new bone area at 2, 4, and 8 weeks.…”
Section: Comparison Of Bone-regenerative Potential Of Different Stem ...mentioning
confidence: 99%
“…After applying cryopreserved ADSCs and DPSCs in a critical-size calvarial defect model, both cryopreserved mesenchymal stem cells significantly improved the bone volume density and new bone area at 2, 4, and 8 weeks. Furthermore, the combined treatment with ADSCs and xenografts was more efficient in enhancing bone repair compared to the combined treatment with DPSCs at all time points [ 201 ]. The authors further evaluated the sequential early bone healing process both histologically and radiographically, confirming a high level of agreement between these two methods, which supports the conclusion [ 201 ].…”
Section: Comparison Of Bone-regenerative Potential Of Different Stem ...mentioning
confidence: 99%
See 2 more Smart Citations